Implementasi Clustering K-Means Terhadap Pemilihan Konsentrasi Mahasiswa Menggunakan Bahasa R - Jimmie; Zulhipni Reno Saputra Elsi; Dedi Haryanto (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Some students in choosing concentration are like friends who don't pay attention to their abilities in that field. It is hoped that this research will form a concentration clustering pattern that is in accordance with the interests and abilities of the students. This grouping information in the selection of student concentration becomes one of the most important information, to get this information is to use the concept of data mining. Data mining is grouped based on the tasks performed, one of which is clustering. Clustering is the process of partitioning a set of data objects into subsets. The K-Means algorithm is a method for grouping objects into a number of K clusters.